A case of successive development of possible acute necrotizing encephalopathy after COVID-19 pneumonia - Pasin Hemachudha; Thanakit Pongpitakmetha; Wanakorn Rattanawong; Poosanu Thanapornsungsuth; Yutthana Joyjinda; Saowalak Bunprakob; Chanida Ruchisrisarod; Thiravat Hemachudha (SAGE Open Medical Case Reports, 2022)
COVID-19 infection often results in an excessive inflammatory response with a spectrum of neurological manifestations. Here, we describe an 81-year-old female with severe COVID-19 pneumonia and subsequent alteration of consciousness after high-dose intravenous dexamethasone and remdesivir. A non-contrast head computed tomography (CT) demonstrated bilateral hypodensities involving bilateral cerebellar hemispheres, thalami, cerebral peduncles and medial parieto-occipital areas. There was no improvement and repeat CT showed progression with findings suggestive of acute necrotizing encephalopathy. Interleukin-6 levels were initially normal; however, subsequent levels were found to be markedly elevated. Acute necrotizing encephalopathy associated with COVID-19 may occur in the setting of severe pneumonia and may represent an immune-mediated process involving inflammatory cytokines such as interleukin-6.
Keywords: Infectious Encephalopathies and Encephalitis; Long-Term Effects of COVID-19; COVID-19 Clinical Research Studies